2006
DOI: 10.4102/jsava.v77i1.339
|View full text |Cite
|
Sign up to set email alerts
|

Partial facial duplication (diprosopus) in a goat kid : clinical communication

Abstract: The anatomical and clinical features of a live-born diprosopic goat kid are described. The kid had two faces with two eyes each, two complete oral cavities and nostrils and two ears. Caudal to the neck, the kid grossly appeared normal. Both mouths of the kid showed synchronous suckling motions. Elevated respiratory and heart rates were recorded and the temperature was subnormal. Radiological examination showed a single trunk and vertebral column, normal limbs, two sets of jaws, three orbits, and contrast radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The external morphological appearance of the present case resembles those described for a similar goat kid (Mukaratirwa & Sayi 2006) which had two faces with two eyes each, two complete oral and nasal cavities and two ears only for the two heads, double sets of jaws caudal to the neck. The kid grossly appeared normal with a single patent oesophagus.…”
Section: Discussionsupporting
confidence: 72%
“…The external morphological appearance of the present case resembles those described for a similar goat kid (Mukaratirwa & Sayi 2006) which had two faces with two eyes each, two complete oral and nasal cavities and two ears only for the two heads, double sets of jaws caudal to the neck. The kid grossly appeared normal with a single patent oesophagus.…”
Section: Discussionsupporting
confidence: 72%
“…Our case has some similarities with the case of a diprosopus of a kid in which there were two partially developed faces with the development of two eyes 24 .…”
Section: Discussionsupporting
confidence: 59%
“…As summarized by these authors, several developmental errors have been suggested as producing diprosopus twins, including duplication of elements derived from the first branchial arch (McLaughlin, ; Maisels, ); split notochord complex (Morton, ; Avery & Hayward, ); sequestration of totipotent cells (Davies et al , ); forking of the notochord; duplications of embryonic structures such as the prosencephalon, the olfactory placodes and the maxillary; mandibular growth centres around the margins of the stomatodeal plate (Barr, ) and duplication of neural crest derivatives (Carles et al , ). Exogenous factors such as hyperthermia, hypoxia, nutritional deficiencies, viral infections, toxins, drugs and chemicals have been proposed as potential inducers of the pathogenetic mechanisms causing diprosopia (Mukaratirwa & Sayi, ). Moreover, genetically encoded morphogenetic disorders have been adduced as possible causes of facial malformations (Mukaratirwa & Sayi, ; Costa et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous factors such as hyperthermia, hypoxia, nutritional deficiencies, viral infections, toxins, drugs and chemicals have been proposed as potential inducers of the pathogenetic mechanisms causing diprosopia (Mukaratirwa & Sayi, ). Moreover, genetically encoded morphogenetic disorders have been adduced as possible causes of facial malformations (Mukaratirwa & Sayi, ; Costa et al , ). Mutation of dlx homeobox genes expressed by neural crest cells (Young et al , ; Depew et al , ; Heude et al , ) might lead to duplication of craniofacial elements (Costa et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation